Pores distribution influences the soil microorganism's response to changes in temperature and moisture (2023)
Microorganisms are an essential fraction of soil organic matter, which presence and activity depend directly on soil physical conditions. This study aimed to address the effect of soil temperature and moisture under contrasting macroporosity conditions on soil biological properties. Soil physical-chemical characterization implicated the collection of composite samples and undisturbed surface soil samples (0 to 10 cm). Also, samples of undisturbed surface soil were extracted in 40 polyvinyl chloride cylinders of 18 cm diameter and 20 cm height for the arrangement of soil mesocosm as the experimental units of a completely randomized experiment with a 2x2x3 factorial arrangement. The experiment duration was 21 days, and the soil biological properties measured were microbial biomass (MB) and soil respiration (SR). Macroporosity showed a significant effect on MB, which indicates that aeration pore influences the number of microorganisms in the soil; for the SR, the macroporosity had a not significant effect. The temperature at the ranges established in the experiment did not significantly affect MB, whereas a highly significant effect of temperature over SR was observed. A highly significant effect of soil moisture was observed on MB and SR. Macroporosity, moisture, and temperature are determining factors in the presence of soil microorganisms, both directly and through the interaction between them. Herein the microorganisms have a wide range of thermal adaptation, and the effect of soil temperature can boost soil microorganisms. In turn, it was observed that the microorganisms present are significantly sensitive to the moisture deficit in soil.